PENGARUH KUALITAS LAYANAN TERHADAPP KEPUASAN KONSUMEN DI JAGUAR FITNES SIDOARJO - effendi, achmad; aji putra, gilang (JEM17: Jurnal Ekonomi Manajemen, 2017)
ABSTRAKThe problem in this research is how big partially and simultaneously influence the quality of service to customer satisfaction at Jaguar Gym Sidoarjo, as well as service quality variables Which most dominant influence on customer satisfaction at Jaguar Gym Sidoarjo.Based on the research results, obtained regression equation as follows: Y = 3.025 + 0.138 + 0.197 X1 + 0.183 X2 + 0,142 X3 X5 + X4 + 0.175 E. Of the acquisition value equation of multiple linear regression model, there are five variables showed a positive coefficient value (tangible, reliability, responsiveness, assurance, empathy), it shows the influence of service quality that is strong enough to customer satisfaction. Keofisien of determination of 0.362, which means that 36.2% variable service quality affects customer satisfaction, while 63.8% are influenced by variables Llain not studied. Based on the results of the multiple correlation coefficient R of 0.602 mind, which means showing that the proportion of the relationship between all the variables of service quality jointly influence on consumer satisfaction and is very strong and positive at 60.2% and the remaining 39.8% influenced by variables investigated. Result research partial test (t test) indicates there is one variable that had no significant effect (tangible) and four other variables (reliability, responsiveness, assurance and empathy) significantly affects satisfaction konsumen.Hasil simultaneous test (F test ) shows that there is significant influence jointly between the variable quality of service (tangible, reliability, responsiveness, assurance, empathy) to customer satisfaction, this is evidenced by the significant value of 0.000. The survey results revealed that the largest beta value contained in the variable reliability of 0,197. So variable reliability has the most dominant influence on consumer satisfaction.Â Kata Kunci :Â  Tangible, reliability, reponsiveness, assurance, empathy.